Microbusiness Mapping Activities to Support Bumdesa Mitra Cibogo Sejahtera Policy in Developing Rural Economies in Desa Cibogo, Kabupaten Tangerang - Kusmulyono, Muhammad Setiawan; Elfriede, Dwining Putri; Raharjo, Taufik (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
Community service activities are carried out with Bumdesa Mitra Cibogo Sejahtera (MCS) located in Cibogo Village, Cisauk District, Tangerang Regency, Banten Province. This collaborative community service activity is carried out using an action research approach to help Bumdesa MCS identify what type of business can be run by Bumdesa MCS in accordance with existing assets and potential. The implementation of this effort is carried out by carrying out business mapping activities for business actors in the Cibogo Village area. The results of the business mapping indicate that Cibogo Village has a variety of business actors engaged in various fields ranging from food and beverage businesses, stalls/small grocery stores, make-up services/salon services, animal shops, laundry services, and fishing equipment shops. The total number of businesses that were successfully mapped during the service activity period was 28 businesses with the food and beverage business dominating reaching 57.14 percent. The follow-up to this business mapping is a discussion to determine the type of business that will be carried out by Bumdesa MCS. A unanimous decision to choose the type of business to be taken has not yet been obtained, but Bumdesa MCS already has a variety of design considerations that will be taken during the Bumdes management deliberation period with the village government in the future.